2016
DOI: 10.3389/fnmol.2016.00080
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Endomorphin-2 and μ-Opioid Receptor in the Spinal Cord Are Associated with Painful Diabetic Neuropathy

Abstract: Painful diabetic neuropathy (PDN) is one of the most common complications in the early stage of diabetes mellitus (DM). Endomorphin-2 (EM2) selectively activates the μ-opioid receptor (MOR) and subsequently induces antinociceptive effects in the spinal dorsal horn. However, the effects of EM2-MOR in PDN have not yet been clarified in the spinal dorsal horn. Therefore, we aimed to explore the role of EM2-MOR in the pathogenesis of PDN. The main findings were the following: (1) streptozotocin (STZ)-induced diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…The current experimental models of PDN are usually made by a single large injection of STZ due to the convenient induction of hyperglycemia [32][33][34]. Due to the selective destruction of pancreatic beta cells, these models are characteristic of rapid onset, weight loss, and insulin deficiency, which can well represent type 1 diabetes, but fail to mimic the pathological process of type 2 diabetes, the predominant subtype of diabetes nowadays, like insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The current experimental models of PDN are usually made by a single large injection of STZ due to the convenient induction of hyperglycemia [32][33][34]. Due to the selective destruction of pancreatic beta cells, these models are characteristic of rapid onset, weight loss, and insulin deficiency, which can well represent type 1 diabetes, but fail to mimic the pathological process of type 2 diabetes, the predominant subtype of diabetes nowadays, like insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether EM2 could change the intrinsic properties of TMR-labeled PNs, the single action potentials (APs) at the threshold and firing patterns (Fig. 5), we use EM2 (3 µM) bath application into the ACSF following our previous studies [20, 31]. No changes were found in the firing pattern test, where EM2 did not change the spike number in most of the recorded TMR-labeled PNs (n = 15, from 8 rats, F (1,70) =1.64, P =0.16, two-way repeated measures ANOVA).…”
Section: Resultsmentioning
confidence: 99%
“…administration of EM2 in the tail-flick, paw-withdrawal, tail pressure and flexor-reflex tests on adult rodents [10, 14-18]. Moreover, it has also been demonstrated that a reduction of EM2 is involved in the chemotherapy-induced neuropathic pain, cancer-induced bone pain, thermal hyperalgesia and inflammatory pain in ovariectomized female rats and painful diabetic neuropathy [14, 17, 19, 20]. However, the underlying mechanisms for these analgesic effect of EM2 in the SDH primarily focused on the morphological and functional studies of the substantia gelatinosa (SG, lamina II) interneurons.…”
Section: Introductionmentioning
confidence: 99%
“…Impairment in the endogenous opioid analgesia system mediated by EM2 via MOR might be involved during the early stage of the PDN [98]. Intracerebroventricular injection of EMs could improve PDN [99].…”
Section: Involvement Of Ems In the Transmission And Modulation Of Noxmentioning
confidence: 99%
“…Intracerebroventricular injection of EMs could improve PDN [99]. This down-regulation of endogenous antinociception may be due to the decreased inhibition of SP signalling resulting from the decreased presynaptic EM2 and MOR expression [94,98].…”
Section: Involvement Of Ems In the Transmission And Modulation Of Noxmentioning
confidence: 99%